Comparison of different strength characteristics of gravel concrete with variable index w/c - Fic, Stanisław; Szewczak, Andrzej (Budownictwo i Architektura / Civil and Architectural Engineering, 2017)
Concrete, as a universal, composite material, is used in structures under the influence of various static, dynamic loads, influences of the external environment, such as sudden impacts, temperature, humidity. Ensuring concrete constructions for safe operation and durability are tasks placed in the design phase, consisting in the testing of mixtures and concrete samples. The studies serve as the most accurate representation of concrete in natural conditions, taking into account the loads during operation. Concrete testing in the laboratory relates to the determination of the compressive strength (fc), the tensile strength (fct); in the area of durability: frost resistance, corrosion resistance, influence of high temperature, absorbability. In the case of concrete durability, the dynamic modulus of elasticity Ed, the stress intensity index (KIC), or the impact of dynamic loads on the durability and strength of concrete are determined – nowadays, they are a rapidly growing test group, which is also related to the emergence of new types of cements, aggregates and consequently new generation concrete, i.e. HSC, UHSC, HPC. Also looking for opportunities to modify and enhance the durability of traditional concrete. Undoubtedly, for all of the aforementioned features of the concrete, the w/c ratio is the decisive factor as the main structural parameter defining the matrix system – aggregate. The paper presents comparative analysis of several strengths of concrete, depending on w/c (values of 0.4-0.7). A fixed amount of aggregate (gravel) was assumed. The influence of the w/c ratio on: fc, fct, KIC, Ei of gravel concrete was analyzed.